Hubungan Ketahanan Keluarga Dengan Kecanduan Game Online Pada Remaja Di SMA Negeri 11 Kota Bekasi - Siti Alifah Nadia Putri (2021)
Technological advances that are increasingly advanced and easy access to the internet, especially in terms of playing online games, make teenagers have to change their behavior in playing online games. Online game games will have an impact on teenagers, one of which is addiction to online games. If teenagers play online games excessively, it will cause health problems in teenagers and the body will feel tired quickly. High family resilience can overcome online game addiction behavior that occurs in adolescents. This study aims to determine the relationship between family resilience and online game addiction in adolescents at SMA Negeri 11 Bekasi City. The method used is descriptive analytic with a cross-sectional approach. The sampling technique used was purposive sampling with a total sample of 293 respondents. Analysis of the data used is univariate analysis and bivariate analysis using the Chi-Square test. The results of this study indicate a relationship between family resilience and online game addiction in adolescents at SMA Negeri 11 Bekasi City (p-value = 0.000). A good level of family resilience will affect the level of adolescent addiction to online games. Adolescents can discuss with their peers about material they do not understand, tell stories with their parents and close people related to the problems they are experiencing and obstacles in dealing with addictive behavior towards online games.